Metal measurement in aquatic environments by passive sampling methods: Lessons learning from an in situ intercomparison exercise. (January 2016) - Dabrin, A.; Ghestem, J.-P.; Uher, E.; Gonzalez, J.-L.; Allan, I.J.; Schintu, M.; Montero, N.; Balaam, J.; Peinerud, E.; Miège, C.; Coquery, M.
Abstract: Passive sampling devices (PS) are widely used for pollutant monitoring in water, but estimation of measurement uncertainties by PS has seldom been undertaken. The aim of this work was to identify key parameters governing PS measurements of metals and their dispersion. We report the results of an in situ intercomparison exercise on diffusive gradient in thin films (DGT) in surface waters. Interlaboratory uncertainties of time-weighted average (TWA) concentrations were satisfactory (from 28% to 112%) given the number of participating laboratories (10) and ultra-trace metal concentrations involved. Data dispersion of TWA concentrations was mainly explained by uncertainties generated during DGT handling and analytical procedure steps. We highlight that DGT handling is critical for metals such as Cd, Cr and Zn, implying that DGT assembly/dismantling should be performed in very clean conditions. Using a unique dataset, we demonstrated that DGT markedly lowered the LOQ in comparison to spot sampling and stressed the need for accurate data calculation. Highlights: Uncertainties on DGT results were assessed during an in-situ intercomparison exercise. DGT handling and analytical procedure steps are responsible for the dispersion of data. Data dispersion was similar between raw data and the TWA concentrations. Abstract : Metal concentrations obtained by DGT during an in-situ intercomparison exercise showed that data dispersion was mainly explained by DGT handling and analytical procedure steps.